Reading errors of dyslexic pupils in Malay language according to Dyslexia Syndrome Theory - Abdan Nasir, Nadia Shuhada; Subramaniam, Vijayaletchumy (Human Resources Management Academic Research Society (HRMARS), 2024)
The aim of this study was to identify dyslexic students' reading mistakes in Malay words in accordance with Levinson's Dyslexia Syndrome Theory (1994). Four dyslexic students from Taman Tun Dr. Ismail, Kuala Lumpur, with a medium reading level in Malay, were the study subjects. Research data was collected using reading test methods, questionnaires, interviews and observations. The research tools included tape recordings, field notes, questionnaires and reading texts. Reading texts are used in reading tests to identify reading errors. The words listed in the reading text are selected according to the learning level of the study subject and the words have 24 syllable structures which are referenced from the Malay Teaching and Learning Guidebook for the Special Rehabilitation Program by the Special Education Division, (Ministry of Education Malaysia, 2019). The results of the analysis from the reading test found that the study subjects had the highest difficulty in spelling words with KVKK syllables that contain the combined consonants /-ng/, diphthongs, paired vowels and digraphs. Levinson (1994)'s Theory of Dyslexia Syndrome is used to analyze each reading error. The results of the analysis found that the study subjects conformed to the characteristics of Levinson's (1994) reading errors, namely elimination, transfer, insertion, substitution, reversal, guessing, except condensation. In the meantime, this study also discovered two other errors that are not within the scope of Levinson's Theory (1994), which are division and pronunciation-type reading errors.